An Optimized Protocol for the Isolation and Functional Analysis of Human Lung Mast Cells - Ravindran, Avinash; Rönnberg, Elin; Dahlin, Joakim S.; Mazzurana, Luca; Säfholm, Jesper; Orre, Ann-Charlotte; Al-Ameri, Mamdoh; Peachell, Peter; Adner, Mikael; Dahlén, Sven-Erik; Mjösberg, Jenny; Nilsson, Gunnar (Frontiers in Immunology, 2018)
Background: Mast cells are tissue-resident inflammatory cells defined by their high granularity and surface expression of the high-affinity IgE receptor, FcεRI, and CD117/KIT, the receptor for stem cell factor (SCF). There is a considerable heterogeneity among mast cells, both phenotypically and functionally. Human mast cells are generally divided into two main subtypes based on their protease content; the mucosa-associated MCT (tryptase positive and chymase negative mast cell) and the connective tissue associated-residing MCTC (tryptase and chymase positive mast cell). Human lung mast cells exhibit heterogeneity in terms of cellular size, expression of cell surface receptors, and secreted mediators. However, knowledge about human lung mast cell heterogeneity is restricted to studies using immunohistochemistry or purified mast cells. Whereas the former is limited by the number of cellular markers that can be analyzed simultaneously, the latter suffers from issues related to cell yield. Aim: To develop a protocol that enables isolation of human lung mast cells at high yields for analysis of functional properties and detailed analysis using single-cell based analyses of protein (flow cytometry) or RNA (RNA-sequencing) expression. Methods: Mast cells were isolated from human lung tissue by a sequential combination of washing, enzymatic digestion, mechanical disruption and density centrifugation using Percoll (WEMP). As a comparison, we also isolated mast cells using a conventional enzyme-based protocol. The isolated cells were analyzed by flow cytometry. Results: We observed a significant increase in the yield of total human lung CD45+ immune cells and an even more pronounced increase in the yield of CD117+ mast cells with the WEMP protocol in comparison to the conventional protocols. In contrast, the frequency of the rare lymphocyte subset innate lymphoid cells group 2 (ILC2) did not differ between the two methods. Conclusion: The described WEMP protocol results in a significant increase in the yield of human lung mast cells compared to a conventional protocol. Additionally, the WEMP protocol enables simultaneous isolation of different immune cell populations such as lymphocytes, monocytes and granulocytes while retaining their surface marker expression that can be used for advanced single-cell analyses including multi-color flow cytometry and RNA-sequencing.